Does Caregiving Cause Psychological Distress? The Case for Familial and Genetic Vulnerabilities in Female Twins. Issue 2 (22nd November 2013) - Vitaliano, Peter P.; Strachan, Eric; Dansie, Elizabeth; Goldberg, Jack; Buchwald, Dedra
Abstract: Background: Informal caregiving can be deleterious to mental health, but research results are inconsistent and may reflect an interaction between caregiving and vulnerability to stress. Methods: We examined psychological distress among 1, 228 female caregiving and non-caregiving twins. By examining monozygotic and dizygotic twin pairs discordant for caregiving, we assessed the extent to which distress is directly related to caregiving or confounded by common genes and environmental exposures. Results: Caregiving was associated with distress as measured by mental health functioning, anxiety, perceived stress, and depression. The overall association between caregiving and distress was confounded by common genes and environment for mental health functioning, anxiety, and depression. Common environment also confounded the association of caregiving and perceived stress. Conclusions: Vulnerability to distress is a factor in predicting caregivers' psychosocial functioning. Additional research is needed to explicate the mechanisms by which common genes and environment increase the risk of distress among informal caregivers.